TRANSFORMATIVE LEARNING AND TEACHING IN FORMATION: How Andragogy as a Model of Formative Teaching Meets Many of the Complex Demands of Veritatis Gaudium - Thannickal, Joseph (Asian Horizons, 2018)
Formation is a matter of deep concern in the Church, and there is an effort all around to make it more effective. The recent document of the Church Veritatis Gaudium contains the Church’s thinking on how formation should be conceptualized and practiced in today’s context. It may be concluded that the expectations of the church today from formation calls for an approach that enhances the transformation of the formee along the path of development of their vocation. That is to say that, a model of formation that is based on the formee’s capacity for transformation is more suited to lead him or her to the renewal of his/her mind and to realize within oneself the image of God. Therefore, the andragogic approach, which is accepted as a model of transformative learning can be a method of choice. An andragogic learning plan prepared for the question of motivation is presented, to demonstrate what andragogy is about and what benefits transformative approaches can bring to religious formation.